Development of A Web-Based Financial of A Vocational High School in Bandung - Maharani, Nadya; Supriyati (Universitas Komputer Indonesia, 2025)
The advancement of information technology has led educational institutions to implement digital systems, including in financial management. SMK ICB Cinta Niaga Bandung faces challenges in revenue recording, which is still done manually, leading to delays, data errors, and audit difficulties. This study aims to design a web-based accounting information system to address these issues. A descriptive qualitative method with the Waterfall model is used. Data were collected through observation, interviews, and documentation. The system was designed using flowcharts, DFDs, ERDs, and user interface design, and developed using PHP and MySQL. Testing results show improved efficiency, reduced recording errors, and structured real-time financial reports. This system is expected to improve transparency and accountability in the school’s financial management. In addition, the system provides several important features, such as multi-user access, secure login, automated financial report generation, and cloud-based data storage. These features allow different stakeholders to access accurate financial information in real-time without the risk of data duplication or loss. The system also facilitates easier monitoring of transactions and ensures that reports can be generated more quickly during audits. Furthermore, the use of digital receipts increases the credibility of financial documentation, reducing the chance of fraud or misreporting. Also included are a number of key functions provided by the system, including multi-user access and authentication (smart login), automatic generation of financial reports and cloud data storage. The features provide a means for different stakeholders to obtain real-time, relevant financial information without the risk of data duplication or loss. The system facilitates the monitoring of transactions and enables faster reporting during audits. Additionally, digital receipts provide a more reliable means of verifying financial information and minimize the risk of fraudulent or inaccurate reporting. Overall, this study contributes to improving financial management practices in vocational schools, particularly those that manage financial flows intricately. The application of information technology not only enhances accuracy and efficiency but also promotes good governance in educational institutions. Hopefully other schools will adopt comparable systems to improve financial responsibility, and perhaps even promote decision-making at different levels of management.